Partial and total skinning vulvectomy in treatment of carcinoma in situ of the vulva - Caglar, H; Delgado, G; Hreshchyshyn, M M (Obstetrics and gynecology (New York. 1953), 1986)
From July 1974 to December 1984, 24 skinning vulvectomies (17 partial and seven total) were performed in 24 patients with carcinoma in situ of the vulva. The objective for partial skinning vulvectomy was preservation of the cosmetic and functional integrity of the vulva in younger and sexually active patients in whom a steady increase in the incidence of vulvar intraepithelial neoplasia has been observed in the last decade. Two groups selected for partial skinning vulvectomy with skin graft were patients with multicentric vulvar intraepithelial neoplasia with colposcopic evidence of normal skin, and patients with localized but a wide surface area of vulvar intraepithelial neoplasia such that poor cosmetic results would be unavoidable should excision be approximated with primary skin closure. Only patients with involvement of the entire vulva were subjected to total skinning vulvectomy with total skin graft replacement. Recurrence and/or persistence were observed in two patients, both treated with total skinning vulvectomy. At present, all 24 patients remain free of detectable neoplasia on follow-up of six months to 11 years and all have very good cosmetic and functional results.